Isolation of Halophilic Bacterial Strains from Mangrove Soil Samples for Polyhydroxyalkanoate Production - Thược, Đoàn Văn; Vóc, Nguyễn Thị (VNU Journal of Science: Natural Sciences and Technology, 2016)
Abstract: More than two hundreds bacterial strains were isolated from mangrove soil samples collected from Quang Ninh province. Among them three of the strains (VK75, VK98 and VK129) were found to accumulate polyhydroxyalkanoate (PHA) in noticeable amounts. Strains VK75, VK98 and VK129 are moderately halophilic, neutrophilic and mesophilic bacteria. The three halophilic bacterial strains were able to synthesize copolymer poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) from various carbon sources (glucose, sucrose, lactose, glycerol, fructose, maltose and molasses). Glucose and glycerol were found to be most suitable substrates for PHBV synthesis by three selected strains. For experiments performed in shake flasks, strain VK75 reached a maximum cell dry weight (CDW) of 3.3 g/l and PHBV content of 67 wt%, strain VK98 attained a maximum CDW of 4 g/l and PHBV yield of 50% while strain VK129 reached a maximum CDW of 4.3 g/l and PHBV content of 56.8 wt% after 36 h of cultivation. The results obtained in this study are comparable to that of the highest reported so far for other moderately halophilic bacteria.   Keywords: Polyhydroxyalkanoate, poly(3-hydroxybutyrate-co-3-hydroxyvalerate), mangrove, halophilic bacteria.